Mutations in COL1A1 Gene Change Dentin Nanostructure. Issue 4 (22nd January 2016) - Duan, Xiaohong; Liu, Zhenxia; Gan, Yunna; Xia, Dan; Li, Qiang; Li, Yanling; Yang, Jiaji; Gao, Shan; Dong, Mingdong
ABSTARCT: Although many studies have attempted to associate specific gene mutations with dentin phenotypic severity, it remains unknown how the mutations in COL1A1 gene influence the mechanical behavior of dentin collagen and matrix. Here, we reported one osteogenesis imperfecta (OI) pedigree caused by two new inserting mutations in exon 5 of COL1A1 (NM_000088.3:c.440_441insT;c.441_442insA), which resulted in the unstable expression of COL1A1 mRNA and half quantity of procollagen production. We investigated the morphological and mechanical features of proband's dentin using atomic force microscope (AFM), scanning electron microscope, and transmission electron microscope. Increased D‐periodic spacing, variably enlarged collagen fibrils coating with fewer minerals were found in the mutated collagen. AFM analysis demonstrated rougher dentin surface and sparsely decreased Young's modulus in proband's dentin. We believe that our findings provide new insights into the genetic‐/nano‐ mechanisms of dentin diseases, and may well explain OI dentin features with reduced mechanical strength and a lower crosslinked density. Anat Rec, 299:511–519, 2016. © 2015 Wiley Periodicals, Inc.